CMD-OPT model enables the discovery of a potent and selective RIPK2 inhibitor as preclinical candidate for the treatment of acute liver injury - Yong Chen; Xue Yuan; Wei Yan; Yurong Zou; Haoche Wei; Yuhan Wei; Minghai Tang; Yulian Chen; Ziyan Ma; Tao Yang; Kongjun Liu; Baojian Xiong; et al. (Acta Pharmaceutica Sinica B, 2025)
Acute liver injury (ALI) serves as a critical precursor and major etiological factor in the progression and ultimate manifestation of various hepatic disorders. The prevention and treatment of ALI is still a serious global challenge. Given the limited therapeutic options for ALI, exploring novel targeted therapeutic agents becomes imperative. The potential therapeutic efficacy of inhibiting RIPK2 is highlighted, as it may provide significant benefits by attenuating the MAPK pathway and NF-κB signaling. Herein, we propose a CMD-OPT model, a two-stage molecular optimization tool for the rapid discovery of RIPK2 inhibitors with optimal properties. Compound RP20, which targets the ATP binding site, demonstrated excellent kinase specificity, ideal oral pharmacokinetics, and superior therapeutic effects in a model of APAP-induced ALI, positioning RP20 as a promising preclinical candidate. This marks the first application of RIPK2 inhibitors in ALI treatment, opening a novel therapeutic pathway for clinical applications. These results highlight the efficacy of the CMD-OPT model in producing lead compounds from known active molecules, showcasing its significant potential in drug discovery.